2022
DOI: 10.29303/j.v2i1.270
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Google Translate Accuracy in Translating Procedural and Narrative Text

Abstract: Translation is an activity to interpret a text from one language to another language without changing the content of the translated text. The objectives this research is: (1) to find out the accuracy of Google Translate in translating Procedural Text and Narrative Text and (2) to investigate which of the two text is translated more accurately comparing to the other text. This research uses descriptive qualitative method. There was one text for each text type, that is procedure text entitled “How to Make Specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, Google Translate may not always accurately translate idiomatic expressions or colloquialisms, which can lead to misunderstandings. Idiomatic expressions and colloquialisms are phrases or expressions that are unique to a particular language or culture and cannot be translated literally (Sumiati, Baharuddin, & Saputra, 2022). For example, the English expression "it's raining cats and dogs" means that it is raining heavily, but the literal translation of this expression in another language may not make sense.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Google Translate may not always accurately translate idiomatic expressions or colloquialisms, which can lead to misunderstandings. Idiomatic expressions and colloquialisms are phrases or expressions that are unique to a particular language or culture and cannot be translated literally (Sumiati, Baharuddin, & Saputra, 2022). For example, the English expression "it's raining cats and dogs" means that it is raining heavily, but the literal translation of this expression in another language may not make sense.…”
Section: Discussionmentioning
confidence: 99%
“…Bowker and Ehgoetz (2007) worked on an empirical study on evaluation of GT texts pointing that google translated textsif left unedited-do not meet the standards of acceptability, accuracy and readability. The study conducted by Sumiati et al (2022) showed that accuracy of google translated texts cannot exceed 80 % in procedural and technical texts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each student might use the tool differently. The previous study stated that the precision of Google Translate in translating procedural and narrative content text shows a high result (Sumiati et al, 2022). It could be because of how well they know English, how good they are with computers or phones, and how well they tell their stories.…”
Section: Introductionmentioning
confidence: 98%
“…They claimed it benefits them when doing the self-learning assisted by the tool (Herlina et al, 2019). When converting procedural and narrative text, the precision of Google Translate is identified to be 79.57% and 86%, which means it is in high regard among students (Sumiati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%